Platelet variables in community-acquired pneumonia in children with respiratory infections - E. A. Kozyrev; I. V. Babachenko; A. V. Orlov; L. A. Alekseeva; E. D. Orlova (Журнал инфектологии, 2022)
Purpose: to assess the relationship of platelet variables with the etiology, severity of community-acquired pneumonia in children and the main biomarkers of systemic inflammation.Object and methods. The study included 65 children aged 9 months to 16 years 11 months with community-acquired pneumonia, who were treated at the clinic of Pediatric Research and Clinical Center for Infectious Diseases and the St. Olga City Children’s Hospital. Upon admission, the children underwent: complete blood count using a hematology analyzer (with the assessment of platelet parameters such as mean platelet volume, platelet distribution width, platelet large cell ratio), blood biochemistry (with the assessment of the C-reactive protein level), chest X-ray with radiographs in two projections. All children were examined for a wide range of pathogens of community-acquired pneumonia: respiratory viruses, S. pneumoniae, H. influenzae type b, M. pneumoniae, C. pneumoniae. The severity of pneumonia was assessed using the modified Respiratory Index of Severity in Children. Depending on the probable etiology, 4 groups of communityacquired pneumonia were identified: bacterial, viral, mycoplasma, and others.The results of the study. No significant differences in platelet variables depending on the etiology of pneumonia were found. In mycoplasma pneumonia, platelet variables are inversely proportional to the total white blood cell count. During the infectious process, all patients showed a significant increase in platelet count. The platelet count on admission directly correlates with the absolute white blood cell count and absolute neutrophil count. There are no significant correlations of platelet count and C-reactive protein concentration.Conclusion. There were no significant differences in platelet count depending on the etiology and severity of pediatric pneumonia. There are features of platelet variables in mycoplasma pediatric pneumonia.